The Influence of Contextual Teaching Learning Models Reviewed from Self-Efficacy on Critical Thinking Ability - Wahyu, Tri Dedy; Kamid, Kamid; Rusdi, Muhammad (PRISMA, 2024)
This study applies a contextual teaching learning model (CTL) which can be a solution for teachers in optimizing the critical thinking skills of students. This research is a queue to make the effect of the CTL application model on the ability to think of students' critical mathematics, the effect of efficacy models of critical thinking critical model critical models of critical models, and objectives, critical mathematics. This research is an experimental study that uses posttest only control design. The population of this study was all students of class X MA Negeri 2 Batanghari Academic Year 2022/2023 as many as 92 students and were divided into 3 classes. In this study, the sample used was 62 students who were divided into two classes (experimental class I and control classes). The sample is determined by a simple random sampling technique. The instruments in this study are a questionnaire for self-efficacy and testing of critical mathematical thinking skills. The data obtained were analyzed using the two-path anova test. The results of this study are the CTL model more effectively affects the ability to think critically mathematics than the category of category category high category more highly interested students with low categories.